Identifikasi Nilai-Nilai Kepemimpinan dalam Wayang Semar Karya Sunan Kalijaga Untuk Mengembangkan Pribadi Konselor - Hafifuddin Nur; Mohamat Hadori (Fakultas Dakwah Universitas Ibrahimy, 2023)
This study aims to identify the leadership values contained in Sunan Kalijaga’s wayang semar, which then these values can be owned and adopted to develop the counselor’s per[1]sonality. The research method used is a qualitative approach type of Layered Hermeneutics. The main data source is in the form of meaning and interpretation of symbolic meaning in Semar’s body which contains the philosophy of leadership written in a book entitled Du[1]nia Semar Abdi Simultaneously Rulers Throughout the Ages by Ardian Kresna. Meanwhi[1]le, supporting data was obtained from interviews with key informants, namely Javanese hu[1]manists who understand the meaning behind the symbols of Semar’s leadership philosophy. The results of the study found nine leadership values taken from Semar’s body including, (1) white tufts have a symbolic meaning of wisdom, (2) looking up face has a symbolic me[1]aning of optimism, (3) eyes and lips, have a symbolic meaning of empathy and give joy, (4) sunthi nose has a symbolic meaning of sensitivity, (5) ears have a symbolic meaning of lis[1]teners, (6) nuding hands have a symbolic meaning of example and role model, (7) seser bun[1]Hafifuddin Nur, Mohamat Hadori hafifuddinnurr@gmail.com, hadorimohamat@gmail.ugm.ac.id Fakultas Dakwah Universitas Ibrahimy Sukorejo Situbondo JURNAL KAJIAN BIMBINGAN DAN KONSELING ISLAM / Volume 2, No. 1, Januari 2023 29 KONSELING AT-TAWAZUN der body has a symbolic meaning of having strong determination and aspirations, ( 8) Po[1]leng village clothing has a symbolic meaning of prioritizing the interests of the people, (9) the position of Semar squatting and standing has a symbolic meaning of serving the people.